MEDITATIONS ON SOME THEONYMS - Sevara Baratova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
In this article, some words are taken from the lexical layer, directly related to theology and human spirituality, which are used a lot in speech, reflecting on the norms of their use in speech and speech. Denotative as well as more connotative meanings of such words have been substantiated on the basis of bytes from the work “Sabot ul-ojizin” by Sowfi Olloyor in Husi.